“The hero in a ghost story laughs a nimble laugh” : The Woman Warrior: Memoirs of a Girlhood Among Ghosts ou la réinvention du canon littéraire états-unien chez Maxine Hong Kingston - Christelle Ha Soon-Lahaye (Caliban: French Journal of English Studies)
In this article, I will show that the numerous ghosts in The Woman Warrior by Maxine Hong Kingston equate the spectrality of minor literatures, especially Chinese American literature, which are somehow still not considered as equally representative of American literature as other works by white writers, as shown by the very fact that they are given a label that points out their specificity even today. The multiplicity of ghosts in the text highlights the difficulty for Chinese Americans to define their identity, and the use of the ghost figure aims at claiming a place and role for Chinese immigrants and their children in American history. The characters’ relations to the ghosts echo the writer’s relation to the national literary canon, as her spectral writing acts as a reminder of the existence of minor literatures, present but all too often forgotten in American literature.